(untitled) (Bangladesh Journal of Neuroscience, 2018)
CAPOS syndrome (cerebellar ataxia, areflexia, pes cavus, optic atrophy, sensorineural hearing loss) is a rare autosomal dominant disorder caused by ATP1A3 mutation. Fever triggered cerebellar dysfunction along with progressive optic atrophy and sensorineural deafness are typical features. Herein, we report a 20-year-old female with multiple fever induced cerebellar dysfunction with partial improvement. Pendular nystagmus and optic atrophy were prominent which were also present in patient’s younger sister. As there was progressive sensorineural hearing loss and areflexia, CAPOS syndrome was diagnosed. Though specific therapy is yet to be developed, acetazolamide, cochlear implantation, visual aid and family screening may improve quality of life. Bangladesh Journal of Neuroscience 2018; Vol. 34 (2): 110-114